Algorithm for Extrapolating Blogger's Interests through Library Classification Systems - Young Sik Kim; Kibeom Lee; Jung-hee Ryu (2008 IEEE International Conference on Web Services, 2008)
All words are used in books, in which each are organized into a category through a library classification system. Therefore, words used by bloggers are also written in books, which in turn are categorized into specific categories. If a blogger uses a particular word often, we can anticipate that the blogger will have interest areas coinciding with the related book categories. This paper suggests that bloggerspsila interests can be known through extracting keywords from blog entry titles and using book classification schemes. Because there were instances in which the keywords alone did not provide adequate information, the Naver (Korean search engine) related keywords search function was used because of its collective intelligence properties. During the experiment, test subjects picked the blogs and entry titles, which were analyzed using the 'Naver OpenAPI'. The results show that it is possible to know a blogger's interests using blog entry titles and book classifications.